Development of Beef Cattle Innovation through “Field Laboratory” Approach - Endang Romjali (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Economic growth in rural areas can be achieved by increasing the productivity of agricultural businesses. Beef cattle breeding farm is managed by small holder farmers with limited ownership integrated with other agricultural activities. This paper aims to provide information on developing beef cattle innovation at farm level through field laboratory (FL) approach or demonstration plot and direct participation with farmers. The development of cattle farming innovation at farm level is limited, hence it is needed to improve the competitiveness of agricultural businesses. Field laboratory is a model for accelerating technology transfer to farmers. The introduction of innovation in beef cattle through LL can be adopted by farmers resulted in increasing the productivity of beef cattle and added value of livestock businesses. For sustainability of technological application it is required supporting facilities and infrastructure such as institutional that provide production and marketing facilities.